Abstract Conference on Scientific & Social Research : Primula Beach Resort, Kuala Terengganu : 10-12 June 2005 / Universiti Teknologi MARA - UiTM, Universiti Teknologi MARA (Universiti Teknologi MARA, 2005)
Contains Title of Abstract, IRPA Abstracts, Social Science Abstracts, and Science & Technology Abstracts.